The impact of governance quality and educational level on environmental performance - Dincă, Gheorghița; Bărbuță, Mihaela; Negri, Camelia; Dincă, Dragoș; Model (Săndulescu), Lizica-Sorina (Frontiers in Environmental Science, 2022)
Environmental degradation and its impact on sustainable development have sparked the interest of national and international policymakers, specialists, and academia. This paper aims to demonstrate the empirical nexus between environmental performance, measured by carbon dioxide emissions, and education levels together with institutional quality in a society. To achieve this goal, the regression model includes the main variables that reflect the quality of governance (government effectiveness, regulatory quality, control of corruption, and rule of law), together with education dimension, gross domestic product, renewable energy consumption, fossil fuel energy consumption, and industry. The data were collected for the 1995 – 2020 period, for a set of 43 countries, consisting of all European Union (EU) members and The Group of Twenty (G20) states. The research uses three estimations methods, respectively Pooled ordinary least squares (Pooled OLS), Fixed effects model (FEM) and Random effects model (REM), together with a two-step dynamic GMM model, to address the endogeneity issue as well. The main results show that all the independent variables reflecting institutional quality from a technical point of view, included in the model when considering the PCSE estimation, have a direct and positive link to CO2 emissions’ level, with control of corruption variable being the only one to influence in a positive manner CO2 emissions at a significant level. Education level, together with economic growth, fossil fuel energy consumption and industry, had a negative significant impact as well upon environmental performance, an increase of one unit in these variables contributing to increased carbon dioxide levels in the EU and G20 sample when considering both the panel corrected model as well as the GMM scenario. Renewable energy is the only independent variable to manifest a significant positive and direct link with environmental performance, drawing attention to the need of adapting the primary sources of energy, in line with international organizations’ sustainable development policy recommendations. Also, there is a need to improve citizens' perceptions of public services and institutions by building confidence in government's ability to formulate and implement regulations.